Angola : Request for Stand-By-Arrangement. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses a request from Angola for a Stand-By-Arrangement (SBA). The requested SBA aims to support orderly policy adjustments to restore macroeconomic balances and rebuild international reserves. This program also includes a focused reform agenda aimed at medium-term structural issues on which long-term non-oil sector growth will ultimately depend. IMF staff and the authorities have agreed that, while the policy mix should consider all possible instruments geared toward achieving these objectives, fiscal policy should play the lead role in the policy package.